2021
DOI: 10.2478/izajolp-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

“Fine...I’ll do it myself”: Lessons from self-employment grants in a long recession period

Abstract: This paper evaluates the effect of a self-employment grant scheme for unemployed individuals—designed to ease the first 12 months of business operation—on firm growth, survival, and labor market reintegration in Croatia in the 2010–2017 period. Grants offered a moderate amount of finances (up to 50% of average annual gross salary) and absorbed only 5% of funds allocated to active labor market policies (ALMPs), but accounted for 10% of new firms opened throughout the years. We contribute to the literature on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For entrepreneurs motivation driven by opportunity, the main role of entrepreneurship policy is to provide entrepreneurial opportunities and support entrepreneurship programs, operations, resources, etc., so as to improve the confidence of college students in entrepreneurship. However, studies have found that government entrepreneurship measures, such as the provision of start-up grants, may have some positive significance in terms of increasing employment, but not for economic growth and entrepreneurial innovation (Caliendo 2016;Srhoj and Zilic 2021), which reminds the government to think about whether the main goal of entrepreneurship policy in the current environment is to create more jobs or to encourage more businesses with good prospects to grow rapidly. College students' capabilities to deal with entrepreneurial risks is obviously weak, so colleges and universities should strengthen the education on entrepreneurial risks, such as the knowledge of risk identification, judgment, and avoidance, so as to improve their risk coping ability and entrepreneurial self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For entrepreneurs motivation driven by opportunity, the main role of entrepreneurship policy is to provide entrepreneurial opportunities and support entrepreneurship programs, operations, resources, etc., so as to improve the confidence of college students in entrepreneurship. However, studies have found that government entrepreneurship measures, such as the provision of start-up grants, may have some positive significance in terms of increasing employment, but not for economic growth and entrepreneurial innovation (Caliendo 2016;Srhoj and Zilic 2021), which reminds the government to think about whether the main goal of entrepreneurship policy in the current environment is to create more jobs or to encourage more businesses with good prospects to grow rapidly. College students' capabilities to deal with entrepreneurial risks is obviously weak, so colleges and universities should strengthen the education on entrepreneurial risks, such as the knowledge of risk identification, judgment, and avoidance, so as to improve their risk coping ability and entrepreneurial self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, individuals feature a high propensity for risk, a strong sense of self-efficacy, and a wealth of resources and they are more likely to view risk as an opportunity, and thus generate entrepreneurial motivation. On the other hand, influenced by external factors, such as entrepreneurship policy, entrepreneurship education (Song and Mu 2022), self-employment grants (Caliendo 2016;Srhoj and Zilic 2021), etc. Usually, strong government measures, financial support, and good entrepreneurship education can mitigate the impact of entrepreneurial risks and encourage more potential entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is that positive effects are often short‐lived as the survival rates of businesses founded by unemployed are relatively low. A sizable portion of subsidized start‐ups closes after a required minimum period of activity (typically 12 months) (Evans & Leighton, 1990; Srhoj & Zilic, 2021). Those surviving usually remain solo and the incidents of “double dividend” derived from additional jobs created are rare (Dvoulety, 2022).…”
Section: Activating Disadvantaged Groups Through (Solo) Self‐employmentmentioning
confidence: 99%
“…The share neither working nor in education is higher than in many OECD countries (Figure 10). This joblessness weighs heavily on those individuals' life-time employment, income and well-being prospects (Schmillen and Umkehrer, 2017 [16]). Efforts are underway to improve the vocational education system, and the preparation for work from schooling, and realising these can help improve the job-readiness of Croatia's youth.…”
Section: Helping Youth Graduate Into Workmentioning
confidence: 99%